Comparison of respiratory fitness and happiness levels in morning and evening walkers - Singh, Priyanka; Singh, Shraddha; Ghildiyal, Archna; Verma, Dileep Kumar (International Journal of Research in Medical Sciences, 2026)
Background: Walking is a simple and widely practised form of physical activity with well-established benefits for respiratory health and psychological well-being. Although exercise timing is known to influence physiological responses through circadian mechanisms, there is a lack of comparative data on the impact of morning versus evening walking on respiratory fitness and happiness in apparently healthy adults. Methods: This cross-sectional analytical study was conducted in the department of physiology, KGMU, Lucknow. Seventy-two apparently healthy adults aged 18-45 years were enrolled and classified as morning walkers (n=36) or evening walkers (n=36) based on their routine exercise timing. Anthropometric and resting cardiovascular parameters were recorded. Respiratory fitness was assessed using the 6-minute walk test (6MWT), and psychological well-being was evaluated using the Oxford happiness questionnaire. Results: Baseline demographic and anthropometric characteristics were comparable between groups. Morning walkers demonstrated a higher mean 6-minute walk distance than evening walkers, though the difference was not statistically significant. The mean happiness index score was also slightly higher among morning walkers. Correlation and regression analyses showed minimal association between happiness scores and anthropometric or pulmonary parameters. Conclusions: Both morning and evening walking were associated with favorable respiratory fitness and happiness levels in healthy adults. Although no statistically significant differences were observed, morning walkers showed a consistent trend toward higher 6-minute walk distance and happiness index scores. These findings indicated that exercise timing did not significantly alter outcomes, while suggesting a possible modest influence of morning activity.